Studies of the correlation between wear behaviour and bonding strength in two types of ceramic coating - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1998)
The plasma-spraying technique is used in this study. Two types of ceramic coating (Al2O3-13wt% TiO2 and Cr2O3-5wt% SiO2-3 wt% TiO2) with and without NiAl bonding coating are subjected to bonding strength and wear tests. Determining the most suitable coating and coating technique and solving an industrial problem are the main objectives of this study. (C) 1998 Kluwer Academic Publishers.
Keywords: ADHESIVE